METHODS OF IMPROVING THE EFFICIENCY OF EXPORT MARKETING IN THE TEXTILE INDUSTRY (Marketing Journal, 2025)
This article explores the ways to improve export marketing in the textile industry. It focuses on the impact of managerial capacity, digital technologies, environmental requirements, and global trade dynamics on export performance. Based on foreign experience and scientific literature, a SWOT analysis and visual evaluation of strategic factors were conducted. The results led to practical recommendations for textile enterprises in Uzbekistan. This study provides a scientific foundation for enhancing the sectorʼs export potential.
Keywords: export marketing; textile industry; digital technologies; environmental standards; SWOT analysis; international experience